Moral Values In Modern Indonesian Literature Works: Personality And Character Education In The Digital Era (Journal of Namibian Studies : History Politics Culture, 2023)
Novel are works that provide examples that can be used as guidelines in family life, the communal environment, education, and the workplace and promote a nation's civilization. A qualitative research design was used, with a novel Arus Balik by Pramoedya Ananta Toer as the object of study. The content analysis approach was combined with the data validity and triangulation methods for data analysis. These resulting in research about moral value is advance proficiency, love, patriotism, bravery, and rasional the findings of this study are intended to show that the has a wealth of moral values rooted in excellence in family, religion, work, education, science, technology, and national culture.